1976
DOI: 10.1083/jcb.71.2.670
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between membrane fluidity and the critical temperature for cell adhesion.

Abstract: BHK 21 cells can adhere to a protein-coated plastic dish in the presence of Ca2+ at temperatures above 12 degrees C. However, they cannot adhere below 8 degrees C. The ESR spectrum of cells spin-labeled with a stearic acid label indicated that the membrane fluidity changed characteristically at 10 degrees C, 20 degrees C, and 30 degrees C. The critical temperature for cell adhesion coincided well with one of the characteristic temperatures for the membrane fluidity change. In the case of adhesion in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…If, however, the cells were then washed and transferred to 37°C, rounding was observed (data not shown). This observation is consistent with a requirement for metabolic energy in cell rounding but may also have been a result of decreasing cell surface receptor mobility because the lipid phase of the cells was frozen (25,37).…”
Section: Effect Of Anti-wga-r On Cell Rounding and Detachmentsupporting
confidence: 73%
“…If, however, the cells were then washed and transferred to 37°C, rounding was observed (data not shown). This observation is consistent with a requirement for metabolic energy in cell rounding but may also have been a result of decreasing cell surface receptor mobility because the lipid phase of the cells was frozen (25,37).…”
Section: Effect Of Anti-wga-r On Cell Rounding and Detachmentsupporting
confidence: 73%
“…Several studies have described Ca 2+ -mediated cell adhesion (Gumbiner, 2005;Halbleib and Nelson, 2006;Lien et al, 2006). Ca 2+ -dependent cell adhesion is reportedly influenced by an increasing incubation temperature (Ueda et al, 1976;Takeichi, 1977). In the present study, spontaneous GGC discharge into PBS [-] from embryonic gonads was mainly observed at 37.8℃ and 42℃, with fewer GGCs discharged at 4℃, 15℃, and 24℃ (Fig.…”
Section: Concentration and Mgmentioning
confidence: 55%
“…A small temperature shift around the phase transition or separation of the lipid bilayer in the membranes is known to bring about drastic changes in the activities taking place in the membranes, e.g. cellular adhesiveness (17), active transport and activities of membrane-bound enzymes (18,21). We are now investigating whether such functional changes are correlated to the physical transition of membranes of D. discoideum cells.…”
Section: Discussionmentioning
confidence: 99%